2009
DOI: 10.1103/physrevc.80.064307
|View full text |Cite
|
Sign up to set email alerts
|

Global nuclear structure effects of the tensor interaction

Abstract: A direct fit of the isoscalar spin-orbit (SO) and both isoscalar and isovector tensor coupling constants to the f 5/2 − f 7/2 SO splittings in 40 Ca, 56 Ni, and 48 Ca nuclei requires a drastic reduction of the isoscalar SO strength and strong attractive tensor coupling constants. The aim of this work is to address further consequences of these strong attractive tensor and weak SO fields on binding energies, nuclear deformability, and high-spin states. In particular, we show that contribution to the nuclear bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…Later on, the two sets of inequalities (3)(4)(5), (6)(7)(8), and the two stability criteria associated to matrices (9) and (10) will be referred to as ℓ = 1, ℓ = 2, J = 1 and J = 2 sets, respectively.…”
Section: Stability Conditions and Landau Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the two sets of inequalities (3)(4)(5), (6)(7)(8), and the two stability criteria associated to matrices (9) and (10) will be referred to as ℓ = 1, ℓ = 2, J = 1 and J = 2 sets, respectively.…”
Section: Stability Conditions and Landau Parametersmentioning
confidence: 99%
“…Recently, and in order to improve the power of the energy density functional derived from the Skyrme interaction, the possibility to incorporate a zero range tensor component to the effective interaction has been explored [4][5][6][7]. In principle, to add tensor components to the effective nucleon-nucleon interaction seems rather natural.…”
Section: Introductionmentioning
confidence: 99%
“…The shape coexistence is analyzed for some N = 28 neutron-rich isotones in [33]. It is shown that whereas the tensor force does not change the ground state the shape coexistence between prolate and oblate states vanishes for 42 Si and 44 S. In the paper by Zalewski et al [27] the contribution of the isovector and isoscalar tensor terms to the binding energy is depicted over the mass table. The impact of two Skyrme functionals on the superdeformed band heads is tested.…”
Section: Introductionmentioning
confidence: 99%
“…They are obtained by studying the structure properties such as the spin-orbit splitting or the single particle energies on the Ca, Ni and Sn chains. In the works of Zalewski et al [26,27] and Grasso et al [28] the spin-orbit strength is modified at the same time that the tensor parameters to reproduce some single particle properties, (spin-orbit splittings) in the doubly magic 40 Ca, 56 Ni and 48 Ca nuclei. The work of Grasso et al enables to reduce the number of parametrizations suggested by Lesinski et al excluding the ones whose parameter signs do not lead to satisfactory results.…”
Section: Introductionmentioning
confidence: 99%
“…This triggered a number of theoretical mean-field [7][8][9][10][11][12][13][14][15][16] and beyond mean-field studies [17][18][19][20]. The conclusion is that the tensor part of the interaction is essential for understanding SE [21].…”
Section: Introductionmentioning
confidence: 99%